UPLC/Q-TOF-MS-based Metabolomics Study of the Antiosteoporosis Effects of Vaccarin in Ovariectomized Mice - Song, Fangming; Xie, Tianyu; Liu, Xi; Chin, Bonnie; Luo, Xiaoting; Liao, Shijie; Abu·Moro; Feng, Wenyu; He, Mingwei; Huang, Nenggan; Su, Zhiheng; Liu, Yun (Planta Medica, 2023)
Osteoporosis is a systemic and metabolic bone disease that usually occurs in postmenopausal women, which mainly manifests as bone loss and increased bone fragility that both facilitate fracture. However, few drugs for osteoporosis have shown good efficacy and limited side effects. Vaccarin has demonstrated its antiosteoporosis effects by inhibiting the formation and osteolytic activities of osteoclasts in our previous investigation. In this study, multivariate statistical analysis and ultrahigh-performance liquid chromatography and quadrupole time-of-flight tandem mass spectrometry were used to analyze the serum metabolites of ovariectomized mice treated with or without vaccarin. As a result, 9 serum metabolites were identified as biomarkers. The metabolic levels of 3 crucial biomarkers, namely, lysophosphatidylcholine [22 : 6, (4Z, 7Z, 10Z, 13Z, 16Z, 19Z)], 1-linoleoylglycerophosphocholine and 1-palmitoyl-Sn-glycero-3-phosphocholine, that were correlated with glycerophospholipid metabolism increased and then decreased significantly after vaccarin treatment. Molecular docking analysis and osteoclasts differentiation experiment further revealed that vaccarin may bind with phospholipase A2 and downregulated its activity to reduce the osteoclastogenesis. Therefore, the occurrence of osteoporosis is closely related with glycerophospholipid metabolism disorders, and vaccarin exerts antiosteoporosis effects by reducing the levels of glycerophospholipid metabolites.
Keywords: postmenopausal osteoporosis; glycerophospholipids metabolism; phospholipase A2; vaccarin; Vaccaria segetalis; Caryophyllaceae